Small Group Discussion For The Students’ Reading Comprehension Of The Senior High School Students - Siregar, Zamila Fitriani; Harida, Eka Sustri; Zainuddin, Zainuddin (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2020)
This studies involved approximately the impact of Small Group Discussion Strategy (SGDS) on the students’ reading comprehension at grade X SMK Swasta Panca Dharma Padangsidimpuan. There had been a few issues determined for the students: 1) they were given problems in comprehending the text, 2) they have problems in deciphering phrases and a few vital components which include predominant idea, normal structure, and particular language features, 3) they had been less practice to the gaining knowledge of process. The purpose of this study is to examine the effectiveness of the SGDS to the students’ reading comprehension. This study turned into experimental studies with pre-test and post-test design. The population turned into all the 10th grade of SMK S Panca Dharma  Padangsidimpuan., they are 112 students; and taken as sample 2 classes, they are XA as experimental group and XB as control group. To examine the information, the researcher used t-test formula.Based at the calculation of t-test, the researcher determined that t-count = 4.18 and t-table = 1.67591, it means that t-count is higher than t-table (4.18 1.67591). So, the researcher should concluded that Ha is accepted and Ho is rejected. It can be concluded that SGDS has big impact to student’s reading comprehension at grade X SMK Swasta Panca Dharma  Padangsidimpuan.